The Resistance in Austria, 1938-1945 - Luza, Radomir V. (Book collections on Project MUSE., 1984)
The Austrians were the first people outside the German Reich to fall under Hitler's rule, and they remained under the Nazi regime longer than any others. For modern Austria -- one of several states created with the collapse of the Habsburg Empire in 1918 -- the interwar years were marked by economic instability and political polarization; the idea of Anschluss -- unification with Germany -- appealed to many Austrians, even though it was expressly forbidden by the 1919 peace treaty. When Anschluss finally happened, in March 1938, it was imposed on Austria by Germany. The change of power went sm.